Digital Transformation of Islamic Boarding School Education - Nugroho, Apriyanto; Astutik, Anita Puji (Indonesian Journal of Islamic Studies, 2024)
This study investigates the integration of digital technology in Tahfidzul Qur’an education within Islamic boarding schools. While education is crucial for human development, boarding schools face challenges such as outdated infrastructure and a heavy curriculum. The research aims to fill the gap in understanding how digital technology affects learning outcomes and student development in Tahfidzul Qur’an education. Using a mixed-method approach, it analyzes quantitative data on student performance and qualitative insights from interviews with teachers, students, and parents. Results show that digital technology positively impacts Tahfidzul Qur’an education by improving memorization, understanding, and application of Qur’anic teachings. However, challenges like limited access to technology and balancing digital and traditional methods persist. Recommendations include providing digital resources and training for teachers to enhance student learning outcomes and prepare them for the digital era while preserving Islamic values. Highlight: 1. Digital integration improves Tahfidzul Qur’an in Islamic boarding schools.2. Balancing tradition and technology for optimal learning outcomes.3. Access to digital resources and teacher training enhances education. Keywords: Islamic education, Tahfidzul Qur’an, digital technology, boarding schools, student development